2016
DOI: 10.1016/j.devcel.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Human Tubulin Proximal to the Kinesin-Binding Site Alter Dynamic Instability at Microtubule Plus- and Minus-Ends

Abstract: The assembly of microtubule-based cellular structures depends on regulated tubulin polymerization and directional transport. Here, we purify and characterize tubulin heterodimers that have human β-tubulin isotype III (TUBB3), and heterodimers with one of two β-tubulin mutations (D417H or R262H). Both point mutations are proximal to the kinesin binding site and have been linked to an ocular motility disorder in humans. Compared to wild-type, microtubules with these mutations have decreased catastrophe frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
101
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 52 publications
11
101
0
Order By: Relevance
“…To purify recombinant forms of different human tubulin isotypes we modified the purification strategy we previously developed to obtain recombinant human β-tubulin, which purified as heterodimers with a mixture of human and insect α-tubulin (Ti et al, 2016). We found that inclusion of an affinity tag on human α-tubulin, similar to the one we used for β-tubulin, substantially reduced protein yield.…”
Section: Resultsmentioning
confidence: 99%
“…To purify recombinant forms of different human tubulin isotypes we modified the purification strategy we previously developed to obtain recombinant human β-tubulin, which purified as heterodimers with a mixture of human and insect α-tubulin (Ti et al, 2016). We found that inclusion of an affinity tag on human α-tubulin, similar to the one we used for β-tubulin, substantially reduced protein yield.…”
Section: Resultsmentioning
confidence: 99%
“…With the development of new purification strategies [24] and expression systems [25,26], it has recently become possible to study more pure tubulin samples from alternative sources. A number of recent structural studies have now used recombinant human tubulin [25,27] and purified yeast tubulin [28] (which is significantly simpler in terms of tubulin isoforms). The latter opens the possibility to carry out parallel in vitro and in vivo studies in the characterization of tubulin mutants, as well as to explore, given the evolutionary distance between yeast and mammalian tubulin, the conservation (or not) of different structural properties between these two MT systems.…”
Section: Structure Of Mts From Alternative Sourcesmentioning
confidence: 99%
“…The results of these studies (3,(32)(33)(34)(35) demonstrate that recombinant tubulins are reliable means to study tubulin isotype-specific effects in vitro and to dissect the role of individual tubulin's CTTs.…”
Section: Introductionmentioning
confidence: 99%
“…fully functional and able to polymerize and form microtubules suitable for motor protein motility and processivity (3,(33)(34)(35). The recombinant human homogeneous microtubules showed different rates of polymerization compared with wild type (32,35).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation